The Effects of TIME-IN on Emotion Regulation, Externalizing, and Internalizing Problems in Promoting School Readiness - Weymeis, Henk; Van Leeuwen, Karla; Braet, Caroline (Frontiers in Psychology, 2021)
Children’s readiness for school is often threatened by the occurrence of both externalizing and internalizing problems. Previous research has shown that Positive Behavioral Interventions and Supports (PBIS) is particularly effective for fostering children’s behavioral skills and reducing externalizing problems. However, whether PBIS can enhance children’s emotional skills and reduce internalizing problems is less clear. Therefore, TIME-IN was developed, which extends PBIS by also including emotional support systems. It was tested whether TIME-IN was effective for (a) improving emotion regulation and (b) reducing depressive symptoms. Furthermore, it was tentatively explored whether TIME-IN is accompanied by more than natural fluctuations in both children’s externalizing and internalizing problems. The effectiveness of TIME-IN was evaluated in a non-randomized study, in which an intervention group was compared with a matched control group. Both research questions were addressed in a sample consisting of 81 children between 8 and 12 years of age with special educational needs. Questionnaires for teachers (i.e. TRF; Achenbach and Rescorla, 2001), children (i.e. FEEL-KJ and CDI; Grob and Smolenski, 2005; Braet et al., 2013; Timbremont and Braet, 2002) and their parents (i.e. CBCL; Achenbach and Rescorla, 2001) were administered at the beginning (T0) and the end of the school year (T1) using multi-informant assessment. Only indicative evidence was found for the hypothesis that TIME-IN improved children’s emotion regulation. Practical implications, strengths, and limitations were discussed.